Travel Industry Economics A Guide for Financial Analysis - Vogel, Harold L. (Springer International Publishing : Imprint: Springer, 2016)
In this book Harold L. Vogel comprehensively examines the business economics and investment aspects of major components of the travel industry, including airlines, hotels, casinos, amusement and theme parks and tourism. The book is designed as an economics-grounded text that uniquely integrates a review of each sector's history, economics, accounting, and financial analysis perspectives and relationships. As such, it provides a concise, up-to-date reference guide for financial analysts, economists, industry executives, legislators and regulators, and journalists interested in the economics, financing and marketing of travel and tourism related goods and services. The third edition of this well-established text updates, refreshes, and significantly broadens the coverage of tourism economics. It further includes new sections on power laws and price-indexing effects and also introduces new charts comparing airline and hotel revenue changes and lodging revenue changes in relation to GDP.